Action Research and Social Movement - Kemmis, Stephen (Education Policy Analysis Archives, 1993)
Large-scale policy research on topics of concern to teachers may assist in changing educational theory, policy and practice, as may educational action research. This article discusses different traditions of action research in relation to their views about the connection of research and social movement, touching on the so-called "macro-micro" problem which bedevils conceptualizations of this relationship.